Assessing the Impact of Chinese Investment on Southeast Africa's Cotton: Moving up the Value Chain? - Tang Xiaoyang (China Africa Research Initiative (CARI), School of Advanced International Studies (SAIS), Johns Hopkins University, 2015)
An influx of Chinese and other Asian investment in Southeast Africa over the last decade has had a significant impact on the cotton-textile value chain in the region. Increased investment has changed the structure of the region's cotton market, increased competition in local markets, introduced new challenges for cotton producers, and affected relationships with local communities. Meanwhile, although the textile sector remains relatively underdeveloped, it has the potential to add value to local cotton sectors if investment continues to increase. Based on extensive fieldwork, this research analyzes the impact Asian investment has had on Southeast Africa's cotton value chain, and identifies strategies for encouraging greater investment from Asian textile manufacturers.
Keywords: 330